Spontaneous and antibody-dependent cell-mediated cytotoxicity by human T cell subpopulations. - Gupta, S (1978)
Human peripheral blood non-T cells, T cells and their subpopulations (Tmu, Tgamma, Tphi, Tgamma-depleted cells, and Tmu-depleted cells) were assayed for their capacity to mediated spontaneous lymphocyte-mediated cytotoxicity (SLMC) or natural killer activity against K562 tumor cell line and antibody-dependent cellular cytotoxicity (ADCC) against chicken erythrocytes coated with antibody. Non-T cells, unseparated T cells, Tgamma cells, and Tmu-depleted (Tgamma-enriched) cells were found to have both SLMC (NK activity) and ADCC. Tmu, Tphi, and Tgamma-depleted cells had minimal or no SLMC and ADCC activity. This study demonstrates that SLMC and ADCC activity in T cells is mediated by Tgamma cell subpopulations. These two cytotoxic reactions were either mediated by two distinct subsets of Tgamma cells or by a single effector cell using two different mechanisms.